The Effectiveness of E-Modules Based on Cognitive Load Theory on Learning Outcomes and Cognitive Load of Vocational High School Students - Fania Komala Sari; Rizki Hikmawan; Andriansyah Setiawan (FKIP - Universitas Riau, 2026)
The goal of this project is to create an e-module with cognitive load management in mind and assess how it affects vocational high school students' learning results. The study uses a pre-experimental experimental design of the one-shot case study type and a descriptive quantitative methodology. A cognitive load questionnaire was used to quantify intrinsic, extraneous, and relevant cognitive load, and a post-test was used to determine learning outcomes. A one-sample binomial test and the Shapiro Wilk normality test were used for data analysis. A binomial test with a significance threshold of 0.035 (<0.05) was employed since the results demonstrated that the data were not normally distributed, suggesting that the e-module design had an impact on student learning outcomes. According to descriptive analysis, the average student learning outcome of 83.33 is classified as